2006
DOI: 10.4269/ajtmh.2006.74.148
|View full text |Cite
|
Sign up to set email alerts
|

Clinic-Based Surveillance for Bacterial- And Rotavirus-Associated Diarrhea in Egyptian Children

Abstract: To identify enteropathogens for vaccine development, we implemented clinic-based surveillance for severe pediatric diarrhea in Egypt's Nile River Delta. Over 2 years, a physician clinically evaluated and obtained stool samples for microbiology from patients with diarrhea and less than 6 years of age. In the first (N = 714) and second clinic (N = 561), respectively, 36% (N = 254) and 46% (N = 260) of children were infected with rotavirus, enterotoxigenic Escherichia coli (ETEC), Campylobacter, or Shigella. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 26 publications
7
60
1
1
Order By: Relevance
“…Despite this, only a few studies report the burden of enteric viruses in North Africa [13,22]. This report, the first comprehensive surveillance describing etiologies of enteric viruses and parasites from children with diarrhea seeking medical care, demonstrated that inclusion of additional laboratory tests significantly The previous publication by our colleagues [7] characterized the frequency of bacterial etiologies of diarrhea in the same region, but in our study, additional analyses illustrated the significance of enteric viral infection in the first year of life in Egyptian children, both as a sole pathogen and as part of what may be a true polymicrobial infection. Also, low prevalence of enteric viruses was observed among children older than a year, which could be partly due to acquired immunity through previous exposures.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Despite this, only a few studies report the burden of enteric viruses in North Africa [13,22]. This report, the first comprehensive surveillance describing etiologies of enteric viruses and parasites from children with diarrhea seeking medical care, demonstrated that inclusion of additional laboratory tests significantly The previous publication by our colleagues [7] characterized the frequency of bacterial etiologies of diarrhea in the same region, but in our study, additional analyses illustrated the significance of enteric viral infection in the first year of life in Egyptian children, both as a sole pathogen and as part of what may be a true polymicrobial infection. Also, low prevalence of enteric viruses was observed among children older than a year, which could be partly due to acquired immunity through previous exposures.…”
Section: Discussionmentioning
confidence: 92%
“…For the majority of these studies, the detection of enteric pathogens was limited to bacteria, and in some studies, Cryptosporidium and RV [5,7,19]. Overall pathogen identification in diarrheal stools was almost 50%.…”
Section: Giardia Lamblia Entamoeba Histolytica Andmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Recently, an ETEC colonization factor was identified in 49% of ETEC isolates from Egypt. 53 In this study CFs were identified in 37.5% (3 of 8) of the ETEC strains examined. Previous studies from Egypt reported closely similar findings with the predominance of CFA/IV, especially CS6 in ETEC strains.…”
Section: Discussionmentioning
confidence: 99%